(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
As online transactions continue to increase and become a significant part of the global economy, the ability to accept payments online becomes more important for businesses. This paper evaluates the literature and provides current information for IS researchers and instructors focusing on electronic commerce. In this paper, we explore the components of e-credit providers (conventional, person-to-person, and third-party) and explain how each system processes a single transaction. We then analyse several market leaders in each segment and summarize the strengths and weaknesses of each company. We provide guidelines for selecting an e-credit provider and highlight the options that apply best to online businesses. Finally, we outline potential areas of future research and provide a simple tutorial on creating a business account with PayPal website Payments Standard as an example of an online payment provider.